Gender dynamics in elementary school teaching: the advantages of men - Santos, M. H. (2018)
This article presents a study that identifies the gender dynamics prevailing in a specific context of tokenism – elementary school teaching – in which the members of an otherwise socially dominant group are proportionally scarce – men. The results contradict Kanter’s (1977) theory by showing that male elementary school teachers do not experience the tokenism dynamics. In line with Williams’ gender perspective and Amâncio’s gender symbolic asymmetry, the article finds that although men constitute a small minority in elementary education, they do not lose the social advantages they generally have: on the contrary, they seem rather to gain several privileges. Indeed, the results show strong links between the tokenism dynamics and gender asymmetry, putting the token men at an advantage. Thus, tokenism seems to be limited to maintaining the gender social order.